PEMBENTUKAN KARAKTER PEDULI LINGKUNGAN SISWA MELALUI KEPRAMUKAAN DI MADRASAH ALIYAH NEGERI 2 BULUKUMBA - Ridha Ichwanty Sabir; M. Rezki (UNM Environmental Journals, 2022)
Scouting activities, including environmental care, are an alternative to shaping student character. The locus of study is the State Aliyah Madrasah (MAN) 2 Bulukumba by analyzing the planning, implementation, and evaluation processes. Data collection activities using the method of observation, interviews and documentation. Researchers apply inductive data analysis to analyze the data. The analysis results show that the scout activities carried out at the research location use the development of students' awareness of the environment. Scoutmasters emphasize the growth of the habit of keeping the practice area and schoolyard clean. In addition, these activities also develop a spirit of sportsmanship and a sense of responsibility in students.